The Effect of Instructional Media and Interpersonal Intelligence on Early Reading Skills - Rani Darmayanti; Dhita Paranita Ningtyas; Siti Roudhotul Jannah; Muhammad Yusuf; Choirudin Choirudin (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
The interaction of kindergarten students with others is dominant in individual activities. It causes low early reading skills. The application of innovative learning media would attract students' interest in interacting with other children and optimize children's interpersonal intelligence. The study examined the effect of instructional media and interpersonal intelligence on early reading skills. This study used to design treatment by level 2 x 2. The selection of this method is based on the existence of treatment with variable attributes based on Interpersonal intelligence levels. Using simple random sampling 44 children were divided into four groups —data Analysis of Variance (ANOVA) and Tukey test. The study concluded that there was a significant difference between the effect of instructional media and media fun thinkers and big books for early reading skills. There was a significant interaction between instructional media and interpersonal intelligence on the early reading skills, (3) for a group that has a high degree of interpersonal intelligence and use fun thinkers media the effect early reading skills is higher than that used big books treatment media. For groups who have lower levels of interpersonal intelligence and used media fun thinkers treatment early reading skills lower than that used big books treatment media